Comparative proteomic and metabolomic analyses reveal resistance mechanisms in Chilli pepper roots of resistant and susceptible varieties to Phytophthora capsici infection - Heng, Zhou; Xu, Xiaowan; Li, Tao; Xu, Xiaomei (Frontiers in Plant Science, 2025)
IntroductionPhytophthora blight, caused by Phytophthora capsici, poses a severe threat to global pepper production.MethodsThis study systematically investigated resistance mechanisms in the root of blight-resistant pepper cultivar CM334 compared to the susceptible genotype NMCA10399 using integrated proteomic and metabolomic analyses at 0, 12, and 36 hour post-inoculation.ResultsThe results showed that arachidonic acid (AA) was the primary differential metabolite between the resistant and susceptible varieties, while the ABC transporter pathway was the main differential protein pathway. The relative content of salicylic acid (SA) showed opposite trends in the early stages of infection in the two varieties. In the resistant variety, proteins involved in plant–pathogen interaction pathways, such as NHO1, Rd19, WRKY1, and WRKY2, were upregulated.DiscussionThis study characterized the differences in metabolite and protein expression profiles between resistant and susceptible pepper varieties after inoculation, identified potential key metabolites and proteins, and provided new theoretical support for the study of pepper blight resistance mechanisms and the breeding of resistant varieties.